2014
DOI: 10.3791/51705
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Source Analysis of High-Density EEG Recordings in Children

Abstract: EEG is traditionally described as a neuroimaging technique with high temporal and low spatial resolution. Recent advances in biophysical modelling and signal processing make it possible to exploit information from other imaging modalities like structural MRI that provide high spatial resolution to overcome this constraint 1 . This is especially useful for investigations that require high resolution in the temporal as well as spatial domain. In addition, due to the easy application and low cost of EEG recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The EEG recordings were exported to EEGLAB format for processing and analysis. The pre-processing pipeline was based on previously described routines (Bathelt et al, 2014). First, the EEG was digitally filtered with finite impulse response (FIR) filters at a high-pass frequency of 0.1 Hz and a low-pass frequency of 30 Hz in EEGLAB 11.0.3 (Delorme and Makeig, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The EEG recordings were exported to EEGLAB format for processing and analysis. The pre-processing pipeline was based on previously described routines (Bathelt et al, 2014). First, the EEG was digitally filtered with finite impulse response (FIR) filters at a high-pass frequency of 0.1 Hz and a low-pass frequency of 30 Hz in EEGLAB 11.0.3 (Delorme and Makeig, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…To this aim, various efforts have been put towards identifying neural markers capable of discriminating between neuropsychiatric disorders, treatment response, and the outcome prediction [ 11 , 12 ]. The electroencephalogram (EEG) has been very helpful, since it allows the brain electrical activity to be recorded in a totally non-invasive manner, with a relative fast montage and a high temporal precision [ 13 , 14 ]. For these reasons, it has been widely used to assess brain function in both the healthy and pathological populations.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies reported significant spatial convergence between ERP and fMRI data. In addition, individual structural MRI images have been combined with EEG/ERP source localization data to construct individual-specific head models for more precise localization in children, adolescents, and adults (Bathelt et al, 2014; Buzzell et al, 2017; Ortiz-Mantilla et al, 2011). In a similar vein, source localization of resting-state EEG data has been combined with resting-state fMRI in epileptic children to locate the neural generators of epileptic spikes (Elshoff et al, 2012; Groening et al, 2009).…”
Section: Introductionmentioning
confidence: 99%